1993
DOI: 10.1104/pp.102.3.967
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Induced by Chrysobactin in Saintpaulia Leaves Inoculated with Erwinia chrysanthemi

Abstract: In this communication, we examine the fate of iron during soft rot pathogenesis caused by Erwinia chrysanthemi on its host, Saintpaulia ionantha. l h e spread of soft rot caused by this enterobacterium was previously shown to depend on a functional genetic locus encoding a high-affinity iron assimilation system involving the catechol-type siderophore chrysobactin. Leaf intercellular fluid from healthy plants was analyzed with regard to the iron content and its availability for bacterial growth. It was compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…Similarly, mutants affected in the achromobactin synthetic genes acsA or acsC cause only localized symptoms (147). Chrysobactin was also detected in plant tissues infected by E. chrysanthemi (354), and a fct-lacZ fusion was strongly expressed in planta during infection (310). These data show that siderophores are important for Erwinia pathogenicity and that iron availability thus plays a major role in regulation of E. chrysanthemi virulence.…”
Section: Induction Of Pectinolytic Enzymes By Iron Limitationmentioning
confidence: 72%
“…Similarly, mutants affected in the achromobactin synthetic genes acsA or acsC cause only localized symptoms (147). Chrysobactin was also detected in plant tissues infected by E. chrysanthemi (354), and a fct-lacZ fusion was strongly expressed in planta during infection (310). These data show that siderophores are important for Erwinia pathogenicity and that iron availability thus plays a major role in regulation of E. chrysanthemi virulence.…”
Section: Induction Of Pectinolytic Enzymes By Iron Limitationmentioning
confidence: 72%
“…Chrysobactin is one of two ferric ion chelators that allow the pathogen to compete with plant cells in iron sequestration (Neema et al, 1993;Dellagi et al, 2005;Dellagi et al, 2009). Arabidopsis treatment with chrysobactin promotes bacterial growth while also activating host SA-regulated responses and expression of FER1 encoding the iron storage protein ferritin (Dellagi et al, 2005;Dellagi et al, 2009).…”
Section: Modifi Cation Of Host Physiologymentioning
confidence: 99%
“…CB and achromobactin production are required for the systemic progression of maceration symptoms on the hosts (Enard et al, 1988;Dellagi et al, 2005;Franza et al, 2005). Neema et al (1993) showed that the production of CB enables bacterial cells to compete with plant cells for iron, preventing sequestration of this metal by the plant ferritins. Consistently, the low availability of iron in the apoplasm of infected Saintpaulia leaves induces the expression of the fct gene, encoding the bacterial outer membrane ferric-chrysobactin (Fe-CB) transporter, which is up-regulated under iron depletion (Masclaux and Expert, 1995).…”
mentioning
confidence: 99%